Awareness and knowledge of breathing exercise as covid-19 management among UTAR students - Loh, Wai Kit (2022)
Background and Objective: COVID-19 is one of the most common disease people faced nowadays. COVID-19 can bring negative effects on our body system especially respiratory system. However, breathing exercise is a very effective method to manage COVID-19 symptoms and benefits in our breathing. Nowadays, University Tunku Abdul Rahman (UTAR) is already conducting the physical classes for their teaching method. Students are requiredto back to the campus and this will lead to physical contact among each other among the students. Eventually the risk of getting COVID-19 may increase among them. However, if they have the awareness and knowledge of breathingexercise to manage COVID-19 symptom, they can recover faster fromCOVID-19 positive and prevent complication from the disease. Hence, the aimof this study is to determine the awareness and knowledge of breathing exerciseas COVID-19 management among UTAR students. Methods: The sampling method used in the study was convenience samplingand the sample size was calculated to be at 415 students. The studyis conducted by sending online questionnaire to the participants Results: The total number of respondents was 415 students, 2 data were removed due to fullfill the exclusion criteria. There are 255 male participants (61.7%) and 158 female participants (51.2%). For the awareness level, 79participants (19.1%) is good, 141 (34.1) is moderate, 181 (43.8%) is poor and12 (3.0%) is no awareness. The mean score is 1.69 with SD = 0.809. For the knowledge level, 62 participants (15.0%) is good, 101 (24.5%) is moderate, 193 (46.7%) is poor and 57 (13.8%) of participants have no knowledge of breathing exercise. The mean is 1.41 with SD = 0.905 Conclusion: In conclusion, most of the participants are in the category of poor awareness and poor knowledge of breathing exercise as COVID-19 management. Breathing exercise is effective in managing the symptomof COVID-19 and should be apply on everyone. Through this research, it canimprove the awareness and knowledge among the people who do not knowbreathing exercise. Future studies in this area are highly recommended.